Peningkatan Pendapatan Masyarakat Melalui Penerapan Teknologi Budidaya Cabe di Pekarangan - Shodiq Eko Ariyanto; Nova Laili Wisuda (Universitas Muria Kudus, 2019)
The high price of chilies will have an impact on family income decreases, therefore to resolve the problem accordingly held a program